On Optical Solitons of the Fractional (3+1)-Dimensional NLSE With Conformable Derivatives - Korpinar, Zeliha; Tchier, Fairouz; Inc, Mustafa (Frontiers in Physics, 2020)
In this article, fractional (3+1)-dimensional nonlinear Shrödinger equation is analysed with kerr law nonlinearity. The extended direct algebraic method (EDAM) is applied to obtain the optical solitons of this equation with the aid of conformable derivative. Optical solitons are investigated for this equation with the aid of the EDAM after the nonlinear Shrödinger equation transformes an ordinary di¤erential equation by using the wave variables trans- formation.